Analisis Fluktuasi Harga Telur Ayam Ras di Provinsi Jawa Timur pada Periode 2019-2023 - Jadmiko, Mochammad Wildan; Amam, Amam; Harsita, Pradiptya Ayu; Arifin, Ahmad Samsul (Universitas Galuh, 2025)
Price fluctuations not only harm consumers when prices increase, but also harm producers and traders when commodity prices decrease. Efforts to control food prices are important to maintain economic stability which has an impact on improving the welfare of society as a whole. Chicken eggs are one of the commodities that often experience price fluctuations. The purpose of this study was to analyze the price fluctuations of chicken eggs and analyze the factors that influence the price fluctuations of chicken eggs in East Java Province in 2019-2023. This study uses the ARCH/GARCH and VAR/VECM model analysis methods. The ARCH/GARCH model analysis is used to analyze the price fluctuations of chicken eggs in East Java Province, while VAR/VECM is used to analyze the factors that influence changes in beef prices in East Java Province. The variables tested include the price of chicken eggs (rupiah/kg), the price of catfish (rupiah/kg) which is a substitute good, the price of rice (rupiah/kg) which is a complementary good, inflation (%), the rupiah exchange rate, and interest rates (%). The results showed that the price of chicken eggs in East Java Province is included in the low fluctuation category. Factors that significantly affect changes in the price of chicken eggs in East Java Province in the short term are the rupiah exchange rate, interest rates, and rice prices; while factors that significantly affect changes in the price of chicken eggs in East Java Province in the long term are inflation, interest rates, and rice prices.